2016
DOI: 10.1007/s11274-016-2167-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and enzymatic hydrolysis of hydrothermally treated β-1,3–1,6-glucan from Aureobasidium pullulans

Abstract: The chemical structure of hydrothermally treated β-1,3-1,6-glucan from Aureobasidium pullulans was characterized using techniques such as gas chromatography/mass spectrometry (GC/MS) and nuclear magnetic resonance (NMR). The chemical shifts of anomeric carbons observed in the C-NMR spectra suggested the presence of single flexible chains of polysaccharide in the sample. β-1,3-1,6-Glucan from A. pullulans became water-soluble, with an average molecular weight of 128,000 Da after hydrothermal treatment, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…APG was kindly provided from Itochu Sugar Co. (Japan), which was prepared according to a previously reported method [[2], [3], [4]]. SPG was purchased from InvivoGen (USA).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…APG was kindly provided from Itochu Sugar Co. (Japan), which was prepared according to a previously reported method [[2], [3], [4]]. SPG was purchased from InvivoGen (USA).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The experiment's planning, design, and data processing correspond to the protocol given in Refs. [1] , [2] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…SPG was purchased from InvivoGen (USA). The water-soluble A. pullulans β-(1→3, 1→6)-glucan was prepared according to a previously reported method [1] , [2] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Recently, the effectiveness of -glucan on respiratory diseases has been studied in rodent [30] and human [31][32][33] because their prevalence has increased rapidly. EAP, exopolymers purified from Aureobasidium pullulans SM-2001, containing 13% -1,3/1,6-glucan [20], are used in test foods and have shown potent immunomodulatory activities in a mouse model [16]. However, this study is the first to evaluate the use of EAP against respiratory diseases.…”
Section: Effects Of Eap Against Colds and Flumentioning
confidence: 98%
“…Dr. Dong-Chan Park). It has been reported that the extracellular polysaccharides isolated from Aureobasidium pullulans are pullulan (poly--1,6-maltotriose-based exopolysaccharide, EPS) [20], aubasidan ( -1,3-D-glucan with -1,6-branches to -1,4 side chains) [21], and -glucan ( -1,3/1,6-D-glucan) [22]. However, the physiological activity of polysaccharides produced by Aureobasidium pullulans has been mainly studied for -1,3/1,6-D-glucan [12].…”
Section: Introductionmentioning
confidence: 99%